2010
DOI: 10.1073/pnas.0912427107
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase Rtt109 is required for Candida albicans pathogenesis

Abstract: Candida albicans is a ubiquitous opportunistic pathogen that is the most prevalent cause of hospital-acquired fungal infections. In mammalian hosts, C. albicans is engulfed by phagocytes that attack the pathogen with DNA-damaging reactive oxygen species (ROS). Acetylation of histone H3 lysine 56 (H3K56) by the fungal-specific histone acetyltransferase Rtt109 is important for yeast model organisms to survive DNA damage and maintain genome integrity. To assess the importance of Rtt109 for C. albicans pathogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 63 publications
8
127
0
Order By: Relevance
“…The link between the SAGA coactivator complex and Hsp90 may help to further explain the importance of this complex in regulating azole resistance. A recent study showed that while the HAT enzyme Rtt109 has no impact on azole sensitivity, it is required for C. albicans pathogenesis in a mouse model of infection (344,634). This is at least partially due to the increased susceptibility to macrophages and the altered profile of metabolic gene expression of the rtt109 homozygous deletion mutant (344) as well as a weaker inflammatory response induced by the rtt109 mutant (634).…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…The link between the SAGA coactivator complex and Hsp90 may help to further explain the importance of this complex in regulating azole resistance. A recent study showed that while the HAT enzyme Rtt109 has no impact on azole sensitivity, it is required for C. albicans pathogenesis in a mouse model of infection (344,634). This is at least partially due to the increased susceptibility to macrophages and the altered profile of metabolic gene expression of the rtt109 homozygous deletion mutant (344) as well as a weaker inflammatory response induced by the rtt109 mutant (634).…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…Finally, reduced levels of H3K56ac activity (regulated by the C. albicans RTT109 gene) have sensitized C. albicans to hydroxyurea, the azoles, and echinocandins and are associated with attenuated C. albicans virulence in mice. 113,120 Inhibition of Hst3p in C. albicans results in loss of cell viability with abnormal filamentous growth. 113 Researchers have tested the activity of at least one new HDACi, MG-CD290, against a range of Candida spp.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Distinct histone chaperones (Vps75 and Asf1) help direct Rtt109 substrate selection for different biological processes, and each stimulates the acetyltransferase activity of Rtt109 (8)(9)(10)(11). In Candida albicans, Rtt109 is required for pathogenesis and, thus, could provide a unique target for antifungal therapies (12). Notably, Rtt109 lacks sequence homology to previously characterized HATs (11,(13)(14)(15), although Rtt109's structure has revealed similarity to the mammalian HAT p300 (KAT3B) (16).…”
mentioning
confidence: 99%